A meta‐analysis on the relationship between posttraumatic growth and resilience in people with breast cancer. Issue 5 (9th December 2022) - Wan, Xiao; Huang, Haitao; Peng, Qianwen; Yu, Nancy Xiaonan; Zhang, Yingming; Ding, Yueming; Wu, Huifang; Hao, Jiwei; Lu, Guangli; Chen, Chaoran
Abstract: Aim: To quantitatively synthesize the correlation between posttraumatic growth and resilience among breast cancer patients and explore the potential moderators affecting the relation. Design: A meta‐analysis of cross‐sectional studies. Methods: This meta‐analysis followed the Preferred Reporting Items for Systematic Review and Meta‐Analyses 2020 guidelines. This meta‐analysis was carried out by searching Chinese and English databases of China National Knowledge Infrastructure, WANFANG DATA, Chongqing VIP Information Co., Ltd., PubMed, Embase, Web of Science, and PsycINFO from inception to February 25, 2022. Pooled Pearson's correlation coefficients between posttraumatic growth and resilience was calculated by the Stata software (version 17.0) using the random effects model. Results: Seventeen studies including 4156 breast cancer patients were identified. A high positive correlation was found between posttraumatic growth and resilience ( r  = 0.448, 95% CI: 0.370–0.519, p  < 0.001), and region and publication type significantly moderated the relation.